2007
DOI: 10.2967/jnumed.106.037556
|View full text |Cite
|
Sign up to set email alerts
|

2-(2-[2-Dimethylaminothiazol-5-yl]Ethenyl)-6- (2-[Fluoro]Ethoxy)Benzoxazole: A Novel PET Agent for In Vivo Detection of Dense Amyloid Plaques in Alzheimer's Disease Patients

Abstract: Extensive deposition of dense amyloid fibrils is a characteristic neuropathologic hallmark in Alzheimer's disease (AD). Noninvasive detection of these molecules is potentially useful for early and precise detection of patients with AD. This study reports a novel compound, 2-(2-[2-dimethylaminothiazol-5-yl]ethenyl)-6-(2-[fluoro]ethoxy)benzoxazole (BF-227), for in vivo detection of dense amyloid deposits using PET. Methods: The binding affinity of BF-227 to amyloid-b (Ab) fibrils was calculated. The binding prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
140
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(146 citation statements)
references
References 33 publications
(31 reference statements)
4
140
0
2
Order By: Relevance
“…[3][4][5] Recent success in developing radiolabeled agents targeting Aβ aggregates has provided a window of opportunity to improve the diagnosis of AD. Preliminary reports of PET imaging suggested that [ 9 showed differential uptake and retention in the brain of AD patients as compared to controls. However, 11 C is a positron-emitting isotope with a short t 1/2 (20 min), which limits its clinical application.…”
mentioning
confidence: 99%
“…[3][4][5] Recent success in developing radiolabeled agents targeting Aβ aggregates has provided a window of opportunity to improve the diagnosis of AD. Preliminary reports of PET imaging suggested that [ 9 showed differential uptake and retention in the brain of AD patients as compared to controls. However, 11 C is a positron-emitting isotope with a short t 1/2 (20 min), which limits its clinical application.…”
mentioning
confidence: 99%
“…As levels of this Aβ subspecies in model mice are m u c h l o w e r t h a n t h o s e i n A D p a t i e n t s (Kawarabayashi et al 2001;Güntert et al 2006), these findings plausibly explain the advantages of high-SA tracers in the sensitive detection of mouse amyloid, and highlight the significance of Aβ -N3-pyroglutamate as a new diagnostic and therapeutic target. The established animal system has been applied to a comparison of multiple radiotracers, such as PIB and 11 C-BF-227 (Kudo et al 2007), in a collaborative work with Tohoku University, and was proven to facilitate the preclinical selection of PET imaging agents adequate for specific purposes, including early detection of amyloid formation, assessment of pathological progression and evaluation of therapeutic effects. Multitracer, multi-scan PET study is also of pivotal importance in the mechanistic evaluation of Aβ immunization and other related anti-amyloid treatments, as a PET ligand for peripheral benzodiazepine receptor, termed […”
Section: Pathological Signatures and Molecular Etiology Of Alzheimer'mentioning
confidence: 99%
“…Several small molecule probes for use with PET have been developed to provide measures of these deposits in vivo. [82][83][84][85][86] The most extensive experience has been with the amyloid-binding radiotracer [ 11 C]-labelled Pittsburgh compound B (2-[4L'-(methylamino)phenyl]-6-hydrobenzothiazole; PIB), a derivative of thioflavin-T amyloid dye that binds to amyloid-β plaques but not tangles. PET studies using [ 11 C]PIB show significantly greater cortical retention in patients with AD compared with controls ( figure 4).…”
Section: Petmentioning
confidence: 99%